The illuminating world of light with Max Axiom, super scientist - Sohn, Emily (Graphic library. Graphic science, 2008)
Max Axiom teaches the science of light, traveling into space, into an eye, and other places to explore such topics as the spectrum, reflection, lasers, and energy conversion.